Mise en evidence des facteurs du paysage agissant sur la repartition de la faune dans une concession forestiere - Vliet, N. van; Nasi, Robert (2007)
In the last 10 years in Central Africa, inventories have been carried out across extensive forest areas in order to support management plans. The aim of these inventories is to assess potential wood resources as well as the diversity of tree species and large mammals. The data products from these inventories presented in this article are derived from multivariate analyses. The study highlights the landscape factors that influence the pattern of fauna distribution in a sustainably managed logging concession in Gabon. The data show that the availability of food resources is not a determining factor in the distribution of fauna scale of the landscape concerned. Some species, such as the blue duiker, brush-tailed porcupine and small diurnal monkeys, do not seem affected by hunting, unlike the red forest duiker. Elephants use areas adjacent to villages and roads. Some species, such as the yeloow-back duiker, avoid their preferred habitat when it is disturbed by human activities, while others are dependent on specific habitats which they occupy in spite of human disturbance. Some populations, which have been rarely observed, deserve to be monitored so that various surprising results can be explained. This study shows that these inventories gain in value with studies of the factors involved in the distribution of fauna in the concession. However, a number of improvements are proposed to facilitate processing for data products. Analyses of this type help to design more effective management directives to take fauna dynamics into account on the scale of the landscape.